Developmental exposure to sertraline impaired zebrafish behavioral and neurochemical profiles - Faria, Melissa; Bellot, Marina; Soto, Oscar; Prats, Eva; Montemurro, Nicola; Manjarrés, Diana; Gómez-Canela, Cristian; Raldúa, Demetrio (Frontiers in Physiology, 2022)
The number of people suffering from mental health problems is rising, with anxiety and depression now the most commonly diagnosed psychiatric conditions. Selective serotonin reuptake inhibitors (SSRIs) are one of the most prescribed pharmaceuticals to treat these conditions, which has led to their common detection in many aquatic ecosystems. As the monoaminergic system shows a high degree of structural conservation across diverse animal phyla, a reasonable assumption is that the environmental levels of SSRIs in surface water can lead to adverse effects on fish and other aquatic wildlife. For instance, Sertraline (SER), a widely prescribed SSRI, has been shown to induce adverse effects in fish, albeit most of the reports used exposure concentrations exceeding those occurring in natural environments. Therefore, there is still a great lack of knowledge regarding SERs effects in fish species, especially during early life stages. This study describes the evaluation of developmental exposure of zebrafish (Danio rerio) to environmentally relevant concentrations of SER (from 0.01 to 10 μg/L), using a battery of key survival behaviors and further relating them with the expression of genes and neurochemical profiles of the monoaminergic system. We found that developmental exposure to SER did not affect embryo morphogenesis and growth. However, concentrations as low as 0.1 μg/L induced hypolocomotion and delayed learning. The observed behavioral impairment was associated with augmented serotonin levels rather than other neurochemicals and molecular markers, highlighting the relationship between serotonin signaling and behavior in zebrafish.